Astaxanthin extraction from Malaysian shrimp waste using High Pressure Processing (HPP) - Irna, Cicy (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Rising of the shrimp production in Malaysia has lead to the accumulation of shrimp waste that caused environmental problems. In fact, the waste can be recovered to produce bioactive compound, such as astaxanthin. Astaxanthin is one of the main carotenoid pigment. It has beneficial effects on the immune system of human body due to powerful antioxidant properties. The application of this bioactive compound is significant in food, pharmaceutical and cosmetic industries. High Pressure Processing method is one of the advanced technology that can be used to extract the bioactive compound more effectively, replacing the conventional extraction methods that have many drawbacks. The goal of this research was first, to screen astaxanthin yield in various species of Malaysian shrimp waste using chemical extraction and High Pressure Processing (HPP) method followed by the optimization of the selected shrimp species to obtain highest astaxanthin yield using HPP. Six types of shrimp species studied were Parapenaeopsis sculptili, Metapenaeus lysianassa, Macrobrachium rosenbergii, Metapenaeopsis hardwickii, Penaeus merguiensis and Penaeus monodon. The optimum condition was achieved at pressure of 238.54 MPa, 16.29 minutes holding time with 6.59 ml mixture solvents of acetone and methanol (7:3, v/v). HPP was proven to have a significant impact to improve the astaxanthin yield. The highest yield of astaxanthin was found in Penaeus monodon species. The optimum yield of astaxanthin was increased from 29.44 µg/gdw, which was treated using chemical extraction to 95.17 µg/gdw treated using HPP. Antioxidant and antimicrobial activity between the optimum astaxanthin yield treated using both HPP chemical extraction were then compared. Antioxidant activities were increased with scavenging activity percentage from 25.47% to 87.90%, reducing activity of ferrum redox reaction from 2.86 µmol TE/g to 8.13 µmol TE/g and oxygen radical absorption capacity from 2,000 µmol TE/100 g to 4,000 µmol TE/100 g. Antimicrobial activity tested using optimum yield of astaxanthin was also increased on four types of bacteria with the highest zone of inhibition of 26 mm against Enterobacter aerogenes, compared to that tested from chemical extraction, with the zone of inhibition of 12.68 mm against same type of bacteria at astaxanthin concentration of 75µg/ml. The comparison between HPP and chemical extraction showed that HPP is more at advantage with higher astaxanthin yield, quality and shorter extraction time. Hence, the ability of HPP to increase astaxanthin yield and its quality from shrimp waste has proven its potential use as an alternative to chemical extraction method.